CATATAN BARU KELELAWAR PEMAKAN NEKTAR (Macroglossus sobrinus) SEBAGAI RESERVOIR LEPTOSPIROSIS DARI INDONESIA - Arief Mulyono; Ristiyanto Ristiyanto; Aryani Pujiyanti; Arum Sih Joharina; Dimas Bagus W.P (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2018)
Epidemiologically bats are important sources of leptospirosis transmission because of their size, abundance, distribution, and their connectivity with domestic animals. The research objective was to detect and identify pathogenic Leptospira species from bats in Wonogiri Regency, Central Java and in Muaro Jambi Regency, Jambi. This research is a descriptive study with a cross-sectional design. The study was conducted from February to March 2017. Detection of Leptospira in bats by PCR technique using specific primers for the 16S rRNA gene. Identification of Leptospira species by comparing the sequence of research results with sequences from GenBank using the BLAST program. Results showed 68 caught bats consisting of 7 genera and 11 species. Bats that detected positive Leptospira were 8 bats consisting from 3 species (Macroglossus sobrinus, Cynopterus brachyotis and Eonycteris spelaela). Detection of pathogenic Leptospira in M. sobrinus is a new record in the world esspecially in Indonesia . Identification of Leptospira sequences from bats showed that one sequence had 98% homology with L. borgpetersenii and another sequence had 97% homology with L.kircheneri.